English Phonological Modification of Teacher Talk for Indonesian Secondary School Students - Muhayyang, Maemuna (Har Press Indonesia, 2022)
Phonological modification of teacher talk is one of crucial things in teaching English as a foreign language for secondary school students. It aims at providing a comprehensible input and language model for students within the efforts of creating effective and meaningful teaching and learning activities designed. Therefore, this study is to explore the ways of employing English phonological modification and the reasons for using it for teaching secondary school students. To gain the data needed, the researcher applied descriptive qualitative research to explore the phenomenon in EFL classroom interaction involving three English teachers who perform their teaching at two different secondary schools in South Sulawesi, Indonesia; SMA Negeri 1 dan 2 Parepare. A direct classroom observation entailing audio recording and interview were utilized to gain the data and analyzed based on the conversational analysis framework. The data analysis reveals that EFL teachers regularly modify their English phonology by using four distinctive features, namely it is more extended pauses, slow rate of speech, exaggerate articulation, and clear articulation. Moreover, these modifications occurred in three numbers of reasons for emphasizing the presented materials, providing understandable and comprehensible input, and modeling the students to the target language. Those findings are taken into account that the use of phonological modification accelerated students’ comprehension in learning English.